Mediation Effect of Job Satisfaction in the Relationship of Organizational Culture and Organization Commitment- Using Process Macro - R, Joiceswarnalatha; V.Murali Krishna, Dr. (International Journal of Engineering and Technology, 2018)
Now-a-days in this IT competitive scenario, it has become quite natural to hear the word job hopping. Most of the IT employeesâ€™ often move from one job to another job. This study is an attempt to find the commitment levels of IT employees in the present scenario. The main objective of the study is to find the impact of organizational culture on the commitment levels of employeesâ€™ and also to find the mediation effect of job satisfaction in the relationship of organizational culture and organization commitment. The sample units have been selected from the region of Hyderabad, Telangana State as it is one of the major IT hubs in India. The sample size of 463 was collected. SPSS Process Macro, Regression is being used for the analysis part. The regression analysis showed significant positive association between organizational culture and organization commitment. The results also showed significant association between organizational culture and job satisfaction. The result of Process Macro showed that job satisfaction mediates in the relationship of organizational culture and organization commitment. Â